Redu????o da maioridade penal: perspectivas e efeitos - Lima, Jandim??rio Teixeira (2017)
Through a bibliographical research, the general objective is to analyze how prospects and the effects that can cause a reduction of the age of majority as well as to verify that only a reduction of the criminal majority is not once a current legislation is not fulfilled. The extension of the maximum period of hospitalization, which could be a majority for five years and up to 21 years when, given the circumstances and high risk of the young person, the measure. The minimum evaluation period may be increased to one year and the judge, if forced to a violation of the internment in serious cases, even if practiced without violence or serious threat. In the first place, there is a measure for a criminal majority, focusing on a historical delay of the age for the imputation of the sentence; In addition to highlighting the biological, psychological and biopsychological criteria and emphasis on comparative law; In the second, the infraction will be approached, entering into juvenile delinquency, the Statute of the Child and Adolescence and as socioeducational measures; and, in the last chapter, it is once the presentation of the paradoxes of reduction in the criminal majority Brazil, containing a PEC 171, as favorable and unfavorable theses, besides the prison situation in Brazil and the constitutionality of the reduction of majority.